Development and Validation of a HPLC Method for Determination of Anastrozole in Tablet Dosage Form - D. Sathis Kumar; A. Harani; D. Sridhar; David Banji; Knv Rao; Guruviah; Yogesw Aran (E-Journal of Chemistry)
A simple, economic, accurate reverse phase isocratic HPLC method was developed for the quantitation of anastrozole in tablet dosage form. The quantification was carried out using Gracesmart RP18, 5 μ (100 mmx4.6 mm) with UV detected at 215 nm. The elution was achieved isocratically with a mobile phase comprising a mixture of buffer (pH 6.0) and acetonitrile (1:1, v/v). The flow rate was 1.0 mL/min The procedure was validated as per ICH rules for Accuracy, Precision, Detection limit, Linearity, Reproducibility and Quantitation limit. The linearity concentration range was 10-20 mcg/mL with the correlation coefficient of 0.9935. The percentage recovery for Anastrozole was found to be 97.31±2.2%. Limit of detection and limit of quantitation values were found to be 0.351 mcg/mL and 1.053 mcg/mL. The method has been successfully used to analyze commercial solid dosage containing 1mg of anastrozole with good recoveries and proved to be robust.